ANALYSIS OF CORPORATE VALUE DEVELOPMENT BASED ON INVESTMENT AND FUNDING DECISIONS, OWNERSHIP STRUCTURE AND DIVIDEND POLICY IN MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Verawaty Verawaty; Citra Indah Merina; Irra Kurniawati (Berkala Akuntansi dan Keuangan Indonesia, 2016)
This study discusses the variables that affect the development of firm value in manufacturing companies on the Indonesia Stock Exchange. The manufacturing sector was chosen as the object of research because the manufacturing sector is directly related to people's daily purchasing power and companies will always produce and require appropriate decisions and policies in terms of the company's financial allocation, so that the development of company value in manufacturing companies is more visible and attractive consideration for investors who want to invest in manufacturing companies. The variables to be analyzed are investment decisions, funding decisions, managerial ownership and institutional ownership, and dividend policy. The population of this study is 138 manufacturing companies Indonesia Stock Exchange (IDX) Fact Book 2013. The results of hypothesis testing indicate that the investment decision variables, managerial ownership, and institutional ownership have a significant influence on firm value. The funding decision variables and dividend policy do not have a significant effect on firm value.